Penapis pemuat tersuis untuk pengukuran akustik - Mohd Alauddin Mohd Ali, (1990)
Switched-capacitor techniques are applied to the design of a bandpass filter circuit satisfying the specification for filters used in acoustical measurement. Dependence of the switched-capacitor filter characteristics on its clock frequency allows the achievement of the whole range of preferred midband frequencies from 10 Hz to 20 kHz by a single circuit. The design produces a circuit which is insensitive to parasitic capacitances and element-value variations. This offers the possibility for the filter and all its accessories to be fully integrated using MOS technology